PENINGKATAN KEMAMPUAN MEMBACA CEPAT DENGAN METODE GERAKMATA MAHASISWA SEMESTER I KELAS A PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Catur Wulandari; Emi Agustina (Universitas Bengkulu, 2018)
The purpose of this study is to improve the ability to read quickly with the method of eye movement of students of Indonesian Language and Literature Study Program semester 1 class A. Method used in this research is PTK conducted in 2 cycles and each cycle is held in 2 meetings. Each cycle is implemented in 4 stages, namely planning, implementation, observation, and reflection. The results showed that the ability to read quickly can be improved by the method of eye movement. This is evident from the results of early tests that indicate the ability to read quickly students of Indonesian Language and Literature Study Program semester 1 Class A there is only 50 kpm. Based on the results of the final test conducted it turns out to increase the ability to read quickly on students. There are 5 texts tested to measure students' fast reading ability, that is text 1 shows there are 22 students reaching KEM above 320 kpm or about 68.75%, in text 2 of 6 or 18.75%, in text 3 there as many as 31 people or 96.9%, text 4 as many as 15 people or 46.9%, and text 5 as many as 12 people or about 37.5%. Text types and text topics determine students' fast reading ability.Keywords: Improvement, Ability, Quick Reading